Նյուտոնի երկրորդ օրենքի և էներգիայի պահպանման օրենքի տրամաբանական կապը - Սողոմոնյան, Ա. Ի.; Ջամալյան, Գ., Ռ․; Զաքարյան, Ա. Ա.; Սողամոնյան, Ռ. Ե․
В статье дается, что на примере одночастичной задачи показано, что для консервативной силы второй закон динамики может быть получе н как следствие закона сохранения энергии. Вывод второго закона Ньютона сделан на основе формул векторной алгебры и известных правил вычисления производной. Полученный результат может считаться дополнительной логической связью в рамках классической механики и имеет важное учебно-методическое значение, так как в традиционных курсах он не затрагивается. Освещенный вопрос может также привести к пересмотру программы раздела “Закон сохранения механической энергии”. By the example of the movement of one particle it was proved that in the case of conservative force we can get the second law of dynamics as a result of the law of conservation of energy. The deduction of Newton’s second law is done on the basis of the formulas of vector algebra and derivative rules. The result that has been acquired may be considered as additional logical link in the framework of the theory of mechanics. Surely, the acquired result is of great educational and methodological importance, as the traditional course of physics doesn’t touch upon the abovementioned question. It can also lead to the reconsideration of the plan in the section of “Laws of conservation of energy”․
Keywords: Ֆիզիկա